The Restaurant Tax Paradox: Bridging Effectiveness and Contribution to Regional Revenue (PAD) in Eastern Indonesia - Sumari, Jenita; Malino, Marlina; Wuriasih, Anik (Penerbit Goodwood, 2025)
Purpose: This research explores the paradoxical nature of restaurant taxation in Manokwari Regency, West Papua, by assessing both the efficiency of tax collection and its contribution to local own-source revenue (PAD) from 2019 to 2023. Methodology/approach: Using a descriptive quantitative method, the study analyzes secondary data from regional financial reports. SPSS version 25 is used to assess the efficiency of tax collection and its contribution to PAD. Pearson correlation and simple linear regression are applied to explore the relationship between the variables. Results/findings: The results show that the effectiveness of restaurant tax collection in Manokwari consistently exceeds annual targets, with an average rate of 108.44%. However, its fiscal contribution to PAD remains modest, averaging only 9.49% per year. Statistical tests indicate a positive but statistically insignificant relationship between collection effectiveness and PAD contribution, with a determination coefficient of only 1%. Conclusions: This study highlights a structural gap between administrative achievement and fiscal impact. This paradox is mainly caused by a narrow tax base, the predominance of micro and informal businesses, and low voluntary compliance. To enhance PAD from the restaurant tax sector, it is essential to expand the tax base, improve fiscal literacy, and strengthen supervision and incentives for restaurant businesses. Limitations: This research is limited to Man okwari Regency and adopts a quantitative approach without incorporating external or qualitative factors. Contribution: This study provides actionable recommendations for optimizing restaurant tax management in developing regions and offers a foundation for further research using broader and mixed-method approaches to achieve a more comprehensive understanding of local tax governance.